Business model innovation: The role of big data analytics capability and entrepreneurial orientation as mediation - Heru Tri Sutiono; Hai Dung Do; Titik Kusmantini; Hendri Gusaptono; Yi Chin Hsieh; Sinta Putri Anggraini; Ashila Metta Rahmadanti (Jurnal Fokus Manajemen Bisnis, 2025)
Big data analytics capabilities are an important tool to business competitiveness high dynamic market conditions. Big data will lead companies to focus more on managing internal and external data with the aim of capturing suitable new opportunities to maintain competitive advantage. Entrepreneurial orientation shows a company’s strategic mindset characterized the willingness take risks, innovate and act proactively in seizing market opportunities for strategic growth. Meanwhile, business model innovation involves deep and last transformations the essential elements firm’s business model. Business model innovation often organizational transformation aimed at ensuring the achievement of expected performance. This study aims to analyze It works closely with the effect big data analytics on business model innovation, acting as a mediating factor in that relationship. This research quantitative method approach. The research population is  oyster mushroom micro small medium entreprises in Sleman, Bantul, and Kulon Progo Regencies and the number of 100 respontents. Study used purposive sampling to select participants. The data was analyzed using structural equation modeling with the partial least squares method. Findings show having strong big data analytics capabilities helps drive business model innovation, and entrepreneurial orientation role process as a mediating variable. Furthermore, entrepreneurial orientation positively affects business model innovation and serves as a mediating variable relationship between big data analytics capability and business model innovation.